1990
DOI: 10.1111/j.1600-0447.1990.tb03069.x
|View full text |Cite
|
Sign up to set email alerts
|

A statistical trial of subclassification for tardive dyskinesia

Abstract: The authors applied a statistical method to subclassify tardive dyskinesia (TD) in 71 psychiatric patients. Based on two-step statistical procedures and findings reported previously, TD is considered to consist of 2 subgroups: a classical dyskinesic group and a dystonic group. Symptoms manifested in the former group are seen most frequently in the oral region while the latter group, which is usually called tardive dystonia, is manifested by movement disorders in the trunk and extremities, predominantly. Abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…We have found evidence of three separate components of TD which closely replicate the findings of Inada et al (1990) and which are in at least partial agreement with other previous reports. Our results differ significantly from Glazer et al (1988) only in the composition of the third factor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have found evidence of three separate components of TD which closely replicate the findings of Inada et al (1990) and which are in at least partial agreement with other previous reports. Our results differ significantly from Glazer et al (1988) only in the composition of the third factor.…”
Section: Discussionsupporting
confidence: 93%
“…Glazer et al (1988) also found three subtypes, namely jaw-tongue, face-lips and extremities. These findings were largely replicated by Inada et al (1990). Thus, limb-truncal and orofacial groupings were found, but the orofacial was divided into facial and lips-jaw-tongue.…”
Section: Introductionmentioning
confidence: 83%
“…2 Inada et al made a statistical distinction between tardive dyskinesia and tardive dystonia. 3 The clinical and physiological backgrounds of tardive dystonia are unclear. However, an existing predisposition to dystonia, which may be triggered by antipsychotics, is likely.…”
Section: Discussionmentioning
confidence: 99%